Prognostic and Therapeutic Implications of Alamandine Receptor MrgD Expression in Clear Cell Renal Cell Carcinoma with Development of Metastatic Disease - Gorka Larrinaga; Jon Danel Solano-Iturri; Inés Arrieta-Aguirre; Asier Valdivia; David Lecumberri; Ane Miren Iturregui; Charles H. Lawrie; María Armesto; Juan F. Dorado; Caroline E. Nunes-Xavier; Rafael Pulido; José I. López; et al. (Biomolecules)
Despite advances in the management of advanced clear cell renal cell carcinoma (ccRCC), robust biomarkers for prognosis and therapeutic response prediction remain elusive. Dysregulation of the intrarenal renin–angiotensin system (RAS) has been implicated in renal carcinogenesis but little explored, particularly regarding biomarker discovery and therapeutic innovation. Consequently, this study investigates the immunohistochemical expression and clinical relevance of the Mas-related G-protein-coupled receptor D (MrgD) in patients with ccRCC who developed metastatic disease (mccRCC). A cohort of 132 patients treated between 2008 and 2018 with nephrectomy and tyrosine kinase inhibitor (TKI)-based sequential therapy was analyzed. Treatment response was assessed using both the MASS and RECIST scoring systems. High MrgD expression in primary tumors was significantly associated with larger size, advanced stage, higher histological grade, and worse overall survival. Among 81 patients with metachronous metastases, high MrgD expression independently predicted shorter disease-free survival. High MrgD staining intensity correlated with poorer TKI responses in first-line therapy but improved outcomes with second-line mTORC1 inhibitors. These findings suggest that MrgD may be a useful biomarker of RAS linked to tumor aggressiveness in ccRCC. MrgD holds potential for identifying high-risk patients and guiding treatment selection in advanced disease. Further research is needed to unlock its clinical potential.